Elements of asymptolic geometry (European Mathematical Society, 2007)
"The book is based on lectures the authors presented at the Steklov Institute in St. Petersburg and the University of Zurich. It is addressed to graduate students and researchers working in geometry, topology, and geometric group theory."--BOOK JACKET